Ultrarapid cryo-arrest of living cells on a microscope enables multiscale imaging of out-of-equilibrium molecular patterns - Huebinger, Jan (2021)
Imaging molecular patterns in cells by fluorescence micro- or nanoscopy has the potential to relate collective molecular behavior to cellular function. However, spatial and spectroscopic resolution is fundamentally limited by motional blur caused by finite photon fluxes and photobleaching. At physiological temperatures, photochemical reactivity does not only limit imaging at multiple scales but is also toxic to biochemical reactions that maintain cellular organization. Here, we present cryoprotectant-free ultrarapid cryo-arrest directly on a multimodal fluorescence microscope that preserves the out-of-equilibrium molecular organization of living cells. This allows the imaging of dynamic processes before cryo-arrest in combination with precise molecular pattern determination at multiple scales within the same cells under cryo-arrest. We both experimentally and theoretically show that ultrarapid cryo-arrest overcomes the fundamental resolution barrier imposed by motional blur and photochemical reactivity, enabling observation of native molecular distributions and reaction patterns that are not resolvable at physiological temperatures.